Cognitive linguistics - Yamanashi, Masaaki 1948- (Sage benchmarks in language and linguistics., 2016)
In the past few decades, cognitive linguistics has developed into one of the most dynamic and empirically significant frameworks within theoretical and descriptive linguistics. It represents a rather broad movement in modern linguistics which includes a variety of approaches and methodologies. They are, however, unified by a number of common assumptions. Foremost among these is the thesis of "cognitive paradigm" (i) language forms an integral part of human cognition, and (ii) any insightful analysis of linguistic phenomena will need to be embedded in what is known about human cognitive abilities. "Cognitive linguistics" aims, therefore, for a cognitively plausible account of what it means to know a language, how languages are acquired, and how they are used. This five-volume Major Work brings together articles on the broad subject of cognitive linguistics, which take up a number of general issues both theoretical and methodological; investigate research questions relating to grammar; explore issues relating to semantic mechanism of language; and outline the relationship between cognitive linguistics and related fields of cognitive science.